Analysis of the Implementation of Cyber Security in Improving Online Transaction Security - Muhammad Iffan; Vebriani Vonie Zatsiyah (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2026)
Digital transformation in the banking sector has driven an increase in the use of online banking services, but also raised the risk of cyber threats that can disrupt the confidentiality, integrity, and trustworthiness of financial transactions. This study investigates how cybersecurity, viewed from a Management Information Systems (MIS) perspective, can improve digital banking transaction security. A systematic literature review using the PRISMA approach was employed. The method used in this study is a systematic literature review with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. The article was searched through Google Scholar with the keywords "cybersecurity", "online banking", "management information systems", "PRISMA," and "banking security", covering 2021-2025, limited to peer-reviewed, English-language, full-text articles. Twenty of the 70 articles found met the inclusion criteria and were analyzed. Results show that technologies such as multi-factor authentication, biometrics, encryption, AI, and blockchain increase user trust and reduce fraud risk. Non-technical elements, such as employee training, security regulations, user awareness, and data management, are equally critical to system resilience. The study confirms that a holistic, integrated cybersecurity strategy within banking MIS is essential. Keywords: Cybersecurity; Online Banking; Management Information Systems; PRISMA; Banking Security